Manual RBC exchange transfusion in a patient of sickle-beta thalassemia syndrome presenting in crisis: a case report - Kanungo, Girija Nandini; Pati, Bibudhendu; Das, Hemlata; Routray, Suman Sudha (International Journal of Advances in Medicine, 2017)
Sickle cell disease and beta thalassemia are caused by abnormal haemoglobin (Hb) derived from mutation of the HBB gene encoding beta-globin. Compound heterozygous status for both mutations results in HbS/beta thalassemia (Sickle- beta thalassemia). Vaso-occlusive phenomena and haemolysis are the clinical hallmarks and major causes of mortality. Here we report a case of successful reduction of HbS level by manual RBC exchange transfusion. Capillary zone electrophoresis showed the case to be Sickle-beta thalassemia. A total of 3 units of 450ml whole blood units were used for manual exchange transfusion done in 2 sittings on consecutive days. Preexchange HbS level was 80.9% of total Hb. HbS level after 24 hours of the second procedure was 44%. In the absence of facility to conduct automated RBC exchange by a cell separator, to reduce HbS in patients presenting with acute complications of SCD and in patients with Vaso-occlusive Crisis, previous stroke, manual RBC exchange can provide a better relief.